Comparison of Hearing Phenotypes Among Children With Congenital Cytomegalovirus and Other Non‐Cytomegalovirus Conditions - Shi Liang; Emily Huang; Jordan Stout; Candace Winterton; Chong Zhang; Bridget F. Dorsey; Angela Presson; Matthew Firpo; Albert Park (OTO Open, 2025)
Abstract Objective Hearing phenotype of the congenital cytomegalovirus (cCMV)‐infected children with isolated sensorineural hearing loss (SNHL) may be distinct from other types of SNHL and may provide an alternative approach for diagnosis. Study Design A retrospective cohort study. Setting Hearing test results of SNHL patients between 2006 and 2022 at Primary Children's Hospital and patients with the following conditions were included: cCMV with isolated SNHL, connexin 26 mutation, enlarged vestibular aqueduct (EVA), and idiopathic. Methods Using 1‐way analysis of variance (ANOVA) tests, we compared each patient's first reliable hearing threshold from 250 to 4000 Hz. The area under the receiver‐operating characteristic (AUROC) curves was calculated for hearing measures in the cCMV and idiopathic groups. The Youden index was then obtained to determine a prediction model for cCMV infection. Finally, plots of various parameters over time were evaluated to compare the cCMV and idiopathic groups. Results A total of 72 patients were evaluated (cCMV: 19; connexin 26: 13; EVA: 24; and idiopathic: 16). The ANOVA test indicated the cCMV group tended to display greater hearing threshold asymmetry (P < .001 vs EVA and connexin, P < .06 vs idiopathic). The ROC curve demonstrated high specificity (0.94) for cCMV infection if the threshold difference between the two ears was greater than 58.6 dB. Comparisons of plots over time suggest no statistically significant difference between the cCMV and idiopathic groups. Conclusion cCMV‐infected children with isolated SNHL can present differently from the other causes of SNHL. The AUROC analysis suggests that a PTA difference greater than 58.6 dB may provide a prediction model to distinguish cCMV from other types of SNHL.